LIPID AND CYTOKINE SPECTRUM LEVELS IN PATIENTS WITH ASTHMA AND OBESITY - Pasieshvili, T. М. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In patients with asthma and obesity studied the performance of proinflammatory cytokines ТNF-α and IL-6 and lipid profile. It is shown that the active inflammatory process in thebroncho-pulmonary system leads to a significant increase of the TNF-α and IL-6, which is due not only inflammation, but also the additional generation of adipose tissue. Lipid profileof these patients is characterized by the formation of the most atherogenic lipoproteins voices, which is considered as an adverse factor in the formation of metabolic disorders.